2007
DOI: 10.1111/j.1365-3156.2007.01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Community participation in Aedes aegypti control: a sociological perspective on five years of research in the health area ‘‘26 de Julio’’, Havana, Cuba

Abstract: Summaryobjective: Effective dengue prevention and Aedes aegypti control is a priority for the Cuban health authorities. To enhance effectiveness, strategies oriented towards a more active involvement of communities in control activities are being tested. This paper presents a sociological perspective on a pilot project conducted in the health area ''26 de Julio'' (La Havana) in 1999-2004.methods: Instrumental case study based on an exhaustive content analysis of project documents and on observations of a socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 20 publications
0
42
0
1
Order By: Relevance
“…Numerous studies have shown the value of community participation in source reduction of container mosquitoes [10], [31], [32], [33]. Community-based programs targeting species, such as Aedes aegypti , have not only been effective in reducing container habitats, but also in reducing house, container, and Breteau indices [7], [31], [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown the value of community participation in source reduction of container mosquitoes [10], [31], [32], [33]. Community-based programs targeting species, such as Aedes aegypti , have not only been effective in reducing container habitats, but also in reducing house, container, and Breteau indices [7], [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although source reduction alone cannot effectively control container mosquitoes [2], these programs can be essential to help reduce potential habitats and sustain source reduction efforts within a community. Although programs that focus on behavior changes through public messages are often short term [34], future community based programs must promote the public to be self-sufficient [33]. Therefore, every effort should be made to involve the community when developing source reduction campaigns [10], [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effects of integrated vector management strategies are likely to be more sustainable as interventions are usually community-based, rather than implemented by specialized teams in a vertical manner. Community-based interventions tend to be sustainable as they aim to change behaviour and induce social mobilization ( Pérez et al , 2007;Toledo Romani et al , 2007 ).…”
Section: Randomly Combinedmentioning
confidence: 99%
“…Este proceso requiere de una propuesta lo suficiente flexible y adaptable y de una metodología que facilite la expresión de la diversidad local. 19 Marta Castro y otros proponen una descripción de la estrategia comunitaria para la prevención del dengue. 20 Los componentes de esta estrategia se definen de manera independiente pero en la práctica se desarrollan de manera cíclica e interactiva y pueden ocurrir simultáneamente, ellos son:…”
Section: La Intervenciónunclassified